Respuesta :
Answer:
-6(x-2)=-7(x-3) = False x = 9
Step-by-step explanation:
Solve for x:
-6 (x - 2) = -7 (x - 3)
Expand out terms of the left hand side:
12 - 6 x = -7 (x - 3)
Expand out terms of the right hand side:
12 - 6 x = 21 - 7 x
Add 7 x to both sides:
7 x - 6 x + 12 = (7 x - 7 x) + 21
7 x - 7 x = 0:
7 x - 6 x + 12 = 21
7 x - 6 x = x:
x + 12 = 21
Subtract 12 from both sides:
x + (12 - 12) = 21 - 12
12 - 12 = 0:
x = 21 - 12
21 - 12 = 9:
Answer: x = 9
Answer:
Step-by-step explanation:
-6(x-2)=-7(x-3)
-6x + 12 = -7x + 21
-6x + 7x = 21 - 12
x = 9